The Relationship Between Narcissistic Behavior and Phubbing Behavior Among Students Who Use Social Media During Classroom Learning Conditions - Mustawin, Siqma Silan Nurul; Amri, Aprilia Kholifatul; Hakiky, Husnadeia Rahma; Prihatiningsih, Riskiyana; Handiastuti, Sri Oetari (Proceedings Series of Educational Studies, 2024)
The rapid development of social media can influence adolescent development. However, behind the convenience offered by technological advances there are dangers that have a negative impact on teenagers. These negative impacts are phubbing behavior and narcissism which can attack teenagers with excessive smartphone use. The absence of previous research that shows a direct relationship between phubbing behavior and narcissism is the basis for this research. The aim of this research is to determine the relationship between narcissistic behavior and phubbing behavior in students who use social media during classroom learning conditions. This research is quantitative correlational research. Sampling used a cluster random sampling technique. The subjects of this research were students in classes X-XI with a total of 92 students. The measuring instrument used in this research is the phubbing and narcissism scale. The hypothesis proposed in this research is that there is a positive relationship between narcissistic behavior and phubbing behavior. The method used for this research is Karl Pearson's Product Moment correlation with the SPSS 25.0 application. The analysis results show a correlation coefficient of r = 0.308. This research hypothesis is accepted by the existence of a significant positive relationship between narcissistic behavior and phubbing behavior. The findings of this research are that there is a significant relationship between narcissism and phubbing in students who use social media during classroom learning conditions. Keywords: phubbing; narcissism; social media addiction